A Prospective Cohort of SARS-CoV-2-Infected Health Care Workers: Clinical Characteristics, Outcomes, and Follow-up Strategy. (8th December 2020) - Nicolás, David; Camós-Carreras, Anna; Spencer, Felipe; Arenas, Andrea; Butori, Eugenia; Maymó, Pol; Anmella, Gerard; Torrallardona-Murphy, Orla; Alves, Eduarda; García, Laura; Pereta, Irene; Castells, Eva; et al.
Abstract: Background: During the coronavirus disease 2019 (COVID-19) outbreaks, health care workers (HCWs) are at a high risk of infection. Strategies to reduce in-hospital transmission between HCWs and to safely manage infected HCWs are lacking. Our aim was to describe an active strategy for the management of COVID-19 in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)–infected HCWs and investigate its outcomes. Methods: A prospective cohort study of SARS-CoV-2-infected health care workers in a tertiary teaching hospital in Barcelona, Spain, was performed. An active strategy of weekly polymerase chain reaction screening of HCWs for SARS-CoV-2 was established by the Occupational Health department. Every positive HCW was admitted to the Hospital at Home Unit with daily assessment online and in-person discretionary visits. Clinical and epidemiological data were recorded. Results: Of the 590 HCWs included in the cohort, 134 (22%) were asymptomatic at diagnosis, and 15% (89 patients) remained asymptomatic during follow-up. A third of positive cases were detected during routine screening. The most frequent symptoms were cough (68%), hyposmia/anosmia (49%), and fever (41%). Ten percent of the patients required specific treatment at home, while only 4% of the patients developed pneumonia. Seventeen patients required a visit to the outpatient clinic for further evaluation, and 6 of these (1%) required hospital admission. None of the HCWs included in this cohort required intensive care unit admission or died. Conclusions: Active screening for SARS-CoV-2 among HCWs for early diagnosis and stopping in-hospital transmission chains proved efficacious in our institution, particularly due to the high percentage of asymptomatic HCWs. Follow-up of HCWs in Hospital at Home units is safe and effective, with low rates of severe infection and readmission.